Assessment of the skill training programme for employment of retrenched female garment workers - Gani, Md. Showkat (BRAC Research and Evaluation Division (RED), 2020)
This study assessed the effectiveness of skill training programme of BRAC for re-employment of retrenched female garment workers (RFGW). Data were collected through in-depth interviews with 20 purposively selected RFGWs and the review of project records. Findings revealed that almost all women found the overall skill training programme very good and effective. The skill training would be more useful if preference is given to the RFGWs for choosing the training type, and the curriculum of the training could be similar. The duration of the 12 days training may be expanded by a few days and the small business trading module may need to be redesigned or cut down from the training programme. BRAC could play a significant role in marketing the goods produced by the RFGWs. Microcredit services were useful for the trained workers who were self-employed in any kind of economic activity. This study concludes that the skill training programme can be suitably linked with BRAC development activities in raising the employment opportunities for the RFGWs.